PENGUJIAN TEORI PECKING ORDER PADA EMITEN SYARIAH DI JAKARTA ISLAMIC INDEX - Fadli Alwi; Nurhalis Nurhalis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to determine the effect of profitability, asset structure, company size and liquidity on capital structure in shariah firm based on the pecking order theory . The research sample consisted of 41 companies listed in the Jakarta Islamic Index (JII) between 2015 and 2019. The method used in this study is panel data regression using the fixed effect model. The results show that: (1) Profitability has significant negative effect on capital (2) Asset structure has a positive and significant effect on capital structure (3) Firm size has a significant positive effect on capital structure (4) Liquidity has a significant negative effect on capital structure. Both profitability and liquidity thus supporting application of the pecking order theory in shariah firm listed in the Jakarta Islamic Index (JII). Investors are expected to consider the effect of profitability, asset structure, company size and liquidity on the structure as investment considerations, while the company is for company funding decisions. Further research, it is advisable to add other factors outside the research variables and increase the number observations of Islamic stocks in Indonesia.